Sejarah dan Metoda Syarah Hadis - Miftah Royyani; Ade Putra; Awaluddinsyah Siregar (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Syarah is a scholar’s attempt to find the meaning of hadith texts. So it can be concluded that sharh hadith is for an explanation of the meaning of the text, pronunciation or sentences related to the hadith of the Prophet Muhammad SAW. This research is a library research and is included in the category of qualitative research. The purpose of this paper is to analyze the science of sharh al-hadith, as well as the history of its development. The results of this study indicate that the syarah of hadith includes: 1) Explaining the quantity and quality of hadith, both from the sanad side and from the matan side, and both global and detailed. This includes an explanation of the paths of transmission, an explanation of the identities and characteristics of the narrators, as well as an analysis of matan in terms of linguistic rules. 2) Describe the meaning and intent of the hadith. This includes explaining how to read certain pronunciations, explaining sentence structure, explaining lexical and grammatical meanings and the intended meaning. 3) Describe the meaning and intent of the hadith. This includes explaining how to read certain pronunciations, explaining sentence structure, explaining lexical and grammatical meanings and the intended meaning. Keywords: Sharia Hadith, History, method